Relationship Between Social Influence, Shopping Lifestyle, and Impulsive Buying on Purchase Intention of Preloved Products - Amaral, Maria Augustin Lopes; Djuang, Gaudensius (KINERJA, 2023)
This research aims to explain consumer buying behaviour on the Internet in three dimensions: shopping lifestyle, social influence, and unplanned purchases that influence consumer intentions to buy used clothes online on Facebook—conducted this research in the city of Kupang, a sample of 215 respondents. The analytical method used is SEM PLS Version 3.0. The results of this study indicate that shopping lifestyle has a significant effect on purchase intention, social influence have a considerable impact on shopping lifestyle and purchase intention, and impulsive buying substantially impacts purchase intention. Therefore, preloved business people need to consider current lifestyles, social influence and impulsive buying to increase recent preloved buying decisions.